First Jurassic dinosaur tracksite from Guizhou Province, China: morphology, trackmaker and paleoecology. (26th November 2019) - Xing, Lida; Lockley, Martin G.; Zhang, Lizhao; Klein, Hendrik; Zheng, Yuanwen; Peng, Guangzhao; Jiang, Shan; Dai, Li; Burns, Michael E.
Abstract: Sauropod tracks from the Early Jurassic Maanshan Member of the Ziliujing Formation in the Dazhuanwan area of Guizhou represent the first Jurassic dinosaur track record for this province. The best preserved and longest trackway is narrow gauge ( Brontopodus type), and indicates a relatively small trackmaker (footprint length 35.0 cm). In conjunction with sauropodomorph skeletal remains these tracks suggest that basal sauropodomorphs and primitive sauropods coexisted in this region during the Early Jurassic. This pattern is same in the Lufeng and Sichuan basins. Thus, sauropod tracks from southwest China are diverse in the Early Jurassic, and include narrow gauge Parabrontopodus, wide gauge Brontopodus -type, and basal sauropodomorph tracks.